Spatiotemporal trends in hernia disease burden and health workforce correlations in aging populations: a global analysis with projections to 2050 - Fangyi Dai; Yuzhou Cai; Huayou Luo; Ruo Shu; Tong Zhang; Yong Dai (BMC Gastroenterology)
Abstract Background Inguinal, femoral, and abdominal wall hernias represent significant health and economic burdens globally, particularly among adults aged 45 and older. In 2021, the Global Burden of Disease Study reported 1.72 million new cases, 6.75 million prevalent cases, and over 41,000 deaths in this population. While age-standardized rates have declined with improved healthcare, absolute burden continues to rise due to population growth and aging. Gender disparities remain pronounced, with men experiencing sevenfold higher incidence than women. This study analyzes global hernia trends, determinants, future projections, and the association between health workforce distribution and hernia burden to inform targeted interventions. Methods Using data from the Global Burden of Disease Study 2021, we analyzed incidence, prevalence, mortality, and disability-adjusted life years (DALYs) for inguinal, femoral, and abdominal wall hernias. Long-term trends were assessed using average annual percentage change (EAPC), with decomposition analyses exploring factors influencing disease burden changes. Spatial and temporal patterns were examined using age-period-cohort and frontier analyses. We conducted health inequality analyses and utilized eight time-series machine learning models to project disease burden from 2022 to 2050. Additionally, we analyzed correlations between health workforce distribution and hernia burden across 204 countries and territories for 1990 and 2019. Results In 2021, global incidence of hernias was 1,720,177, with 6,748,203 prevalent cases and 41,834 deaths among individuals aged 45 years and older. Although age-standardized incidence rate (ASIR) decreased from 153.98/100,000 in 1990 to 112.29/100,000 in 2021 (EAPC = -0.83%, 95% CI: -0.95% to -0.70%), and age-standardized mortality rate (ASMR) decreased from 3.19/100,000 to 1.86/100,000 (EAPC = -1.77%, 95% CI: -1.94% to -1.59%), absolute burden continued increasing. Socioeconomic differences were significant, with higher ASIR in high SDI areas (141.94/100,000) than low SDI areas (104.60/100,000) in 2021, but much higher ASMR in low SDI areas (4.14/100,000) than high SDI areas (1.23/100,000). Decomposition analysis revealed population growth as the main driver of increased disease burden, contributing 173.80% to incidence increases. Age-period-cohort analysis showed incidence peaked in the 65–69 age group (RR = 1.43, 95% CI: 1.42–1.43). Male ASIR in 2021 (203.41/100,000) was approximately 7.3 times higher than female ASIR (27.94/100,000). Correlation analyses revealed significant negative associations between pharmaceutical personnel density and hernia disease burden, with correlation coefficients strengthening from 1990 (DALYs: r = -0.39, p < 0.001) to 2019 (DALYs: r = -0.57, p < 0.001). Similar trends were observed for dentistry personnel (DALYs: r = -0.26 in 1990 to r = -0.47 in 2019, p < 0.001). Countries with high hernia burden (Guatemala, Paraguay, Indonesia) consistently demonstrated lower health workforce density compared to low-burden countries. ARIMA model projections showed that by 2050, ASIR would increase slightly from 112.32/100,000 in 2022 to 112.64/100,000, with absolute new cases increasing by 19.70%. ASMR is projected to increase from 1.84/100,000 to 2.11/100,000, with deaths increasing by 8.50%. Conclusions Despite declining age-standardized rates for inguinal, femoral, and abdominal wall hernias, absolute disease burden continues increasing due to demographic factors. Socioeconomic development significantly impacts disease patterns, with higher morbidity but lower mortality in high SDI areas. The strong negative correlation between pharmaceutical and dentistry personnel density and hernia burden suggests potential protective effects of healthcare workforce investment, particularly in resource-constrained settings. Future projections indicate growing absolute burden despite relatively stable age-standardized rates, highlighting the urgent need to strengthen preventive measures, improve treatments, and strategically allocate health workforce resources to address this growing public health challenge.